Isolation and characterization of a new [FeFe]‐hydrogenase from Clostridium perfringens. (1st July 2015) - Morra, Simone; Mongili, Beatrice; Maurelli, Sara; Gilardi, Gianfranco; Valetti, Francesca
Abstract: This paper reports the first characterization of an [FeFe]‐hydrogenase from a Clostridium perfringens strain previously isolated in our laboratory from a pilot‐scale bio‐hydrogen plant that efficiently produces H2 from waste biomasses. On the basis of sequence analysis, the enzyme is a monomer formed by four domains hosting various iron–sulfur centres involved in electron transfer and the catalytic center H‐cluster. After recombinant expression in Escherichia coli, the purified protein catalyzes H2 evolution at high rate of 1645 ± 16 s −1 . The optimal conditions for catalysis are in the pH range 6.5–8.0 and at the temperature of 50 °C. EPR spectroscopy showed that the H‐cluster of the oxidized enzyme displays a spectrum coherent with the Hox state, whereas the CO‐inhibited enzyme has a spectrum coherent with the Hox ‐CO state. FTIR spectroscopy showed that the purified enzyme is composed of a mixture of redox states, with a prevalence of the Hox ; upon reduction with H2, vibrational modes assigned to the Hred state were more abundant, whereas binding of exogenous CO resulted in a spectrum assigned to the Hox ‐CO state. The spectroscopic features observed are similar to those of the [FeFe]‐hydrogenases class, but relevant differences were observed given the different protein environment hosting the H‐cluster.